INCONSISTENCY OF LAWS ON ERADICATION OF CORRUPTION IN INDONESIA - Gustian, Leo; ansah, Ardi; Kadaryanto, Bagio (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
ABSTRACT The inconsistency of the law on eradicating criminal acts of corruption in Indonesia, especially regarding criminal acts of corruption in office or related to office, apart from not conflicting with the legal hierarchy in Indonesia, also causes the absence of legal certainty in law enforcement against criminal acts of corruption, especially corruption in office or related matters. Related to position and ostensibly to provide wide latitude for state administrators/state officials who are caught in criminal acts of bribery to escape punishment. The ideal legal concept for eradicating criminal acts of corruption in Indonesia, especially regarding criminal acts of corruption in office or related to office, is the ideal concept in Article 3 and Article 4 of Law Number 19 of 2019 concerning the Second Amendment to Law Number 30 of 2002 concerning Commissions. Eradication of Corruption Crimes. The phrase